Húngaros en los trópicos. Rosti Pál y otros viajeros en el Caribe y en América Central en la segunda parte del siglo XIX - Jancsó, Katalin (Acta Hispanica, 2013)
The aim of our study is to give a panoramic view of the Hungarian emigration to the Caribbean and Central America during the nineteenth century, concentrating on travelers who arrived to the above mentioned region. We emphasize three distinguished figures, first trying to present briefly Sámuel Wass and Jenő Bánó. We dedicate the second part of the study to a more detailed description of the photographer, Pál Rosti’s journey to America and his work.